A Content Analysis of the Friday Sermons of the Turkish-Islamic Union for Religious Affairs in Germany (DİTİB) - Sarah Carol; Lukas Hofheinz (Politics and Religion, 2022)
The Turkish-Islamic Union for Religious Affairs (DİTİB) runs more than 900 mosques in Germany and circulates Friday sermons in these mosques. Our analysis provides a nuanced depiction of the link to the homeland by conducting qualitative and quantitative content analyses of 481 sermons from 2011 to 2019. To what extent are relations with Turkey reflected in the sermons? And how is the concept of "home" reflected in those sermons? While homeland-related issues constitute a minority overall, the concept "home" occurs in five different contexts within these sermons: First, sermons directly refer to the homeland and norms connected to it. Second, implicit links are created by discussing events in Turkey. Third, leaving the homeland is described as an integral part of the history of Islam. The last two contexts discuss Germany as a "new home", and build links to Turkey's Directorate of Religious Affairs (Diyanet) through its foundation.
Keywords: 330; DİTİB; Islam; mosques; content analysis; Friday sermons